Multi-targeted loss of the antigen presentation molecule MR1 during HSV-1 and HSV-2 infection - Carolyn Samer; Hamish E.G. McWilliam; Brian P. McSharry; Thilaga Velusamy; James G. Burchfield; Richard J. Stanton; David C. Tscharke; Jamie Rossjohn; Jose A. Villadangos; Allison Abendroth; Barry Slobedman (iScience, 2024)
Summary: The major histocompatibility complex (MHC), Class-I-related (MR1) molecule presents microbiome-synthesized metabolites to Mucosal-associated invariant T (MAIT) cells, present at sites of herpes simplex virus (HSV) infection. During HSV type 1 (HSV-1) infection there is a profound and rapid loss of MR1, in part due to expression of unique short 3 protein. Here we show that virion host shutoff RNase protein downregulates MR1 protein, through loss of MR1 transcripts. Furthermore, a third viral protein, infected cell protein 22, also downregulates MR1, but not classical MHC-I molecules. This occurs early in the MR1 trafficking pathway through proteasomal degradation. Finally, HSV-2 infection results in the loss of MR1 transcripts, and intracellular and surface MR1 protein, comparable to that seen during HSV-1 infection. Thus HSV coordinates a multifaceted attack on the MR1 antigen presentation pathway, potentially protecting infected cells from MAIT cell T cell receptor-mediated detection at sites of primary infection and reactivation.